Plongée dans les métaphores et représentations liquides de la société numérique - Marc Bernardot (Netcom)
Digital jargon uses a lot of liquid words. What do these liquid metaphors base and shape? What do they show and hide ? Are they used as an alive metaphor, or a degraded, nomadic or “spongious” one? This article is divided in three parts to try to answer these questions. The first part describes various employment of the “liquid” semantic field as it is mobilized both in technic lexicons, in collective imagination and in cognitive frameworks of Internet pionniers and current actors (1.). In a second part the analysis focuses on the way how the negative and cataclysmic narratives of digital society are discursively shaped and based on “liquid” depictions of opacity, leaks and uncontrolled floods of informations and money’s diversion (2.). The third part examines some utopic and positive outlooks of the network technologies when they apply the semantic field of liquidity to describe the progresses in transparency, fluency, mobility due to the digital economy (3.). The conclusion explore theorical and political prospects propelled by the liquid metaphors as well as the issues of these ambivalent interpretativ readings of the future of digital era, to make the point on the tension between the fear of “liquid” global watch and the hope of a domination systems's “liquidation”.